2009
DOI: 10.1007/s11092-009-9071-5
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining continued acceleration in reading comprehension achievement following an intervention

Abstract: Schooling improvement initiatives have demonstrated that moderate but significant achievement gains are possible with well designed interventions, but there is little research into whether these gains can be sustained. The present study examines the extent to which acceleration in achievement made during a three-year literacy intervention and the associated school-based practices were continued. Statistical modelling showed continued acceleration in student achievement (four months in addition to expected prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
46
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 10 publications
1
46
0
Order By: Relevance
“…The primary reason for this is that we expect teachers to make high-quality decisions, which requires their decisions to be based not only on experience and intuition but also on data. Several studies have shown that data use can lead to school improvement in terms of increased student achievement (Campbell & Levin, 2009;Carlson, Borman, & Robinson, 2011;Lai, McNaughton, Timperley, & Hsiao, 2009;McNaughton, Lai, & Hsiao, 2012). Teachers can use data, such as assessment data and classroom observation data, to determine the learning needs of their students, and to adapt their instruction according to these learning needs.…”
Section: Introductionmentioning
confidence: 99%
“…The primary reason for this is that we expect teachers to make high-quality decisions, which requires their decisions to be based not only on experience and intuition but also on data. Several studies have shown that data use can lead to school improvement in terms of increased student achievement (Campbell & Levin, 2009;Carlson, Borman, & Robinson, 2011;Lai, McNaughton, Timperley, & Hsiao, 2009;McNaughton, Lai, & Hsiao, 2012). Teachers can use data, such as assessment data and classroom observation data, to determine the learning needs of their students, and to adapt their instruction according to these learning needs.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, teachers may change their behavior, such as by trying out different instructional strategies, which can improve their own performance (Schildkamp and Kuiper, 2010) and lead to improved student achievement (Campbell and Fullan, 2006;Carlson et al, 2011;Lai et al, 2009).…”
mentioning
confidence: 99%
“…Staff, students, and contexts change, so that what used to be effective and worked at one point in time may become ineffective when students change or new teachers come into the school (Lai, McNaughton, Timperley, et al, 2009). Teachers and school leaders need data to help monitor their constantly changing environment -what has changed and to what extent are curriculum aims and staff and student needs being met -so that they are able to react in a timely and evidence-based manner to uncover and solve new problems.…”
Section: Rationale For Data-based Decision Makingmentioning
confidence: 99%
“…Growing evidence exists that data use can lead to school improvement in terms of increased student achievement levels (Campbell & Levin, 2009;Carlson et al, 2011;Cawelti & Protheroe, 2001;Lai, McNaughton, Amituanai-Toloa, Turner, & Hsiao, 2009;Lai, McNaughton, Timperley, et al, 2009;McNaughton et al, this issue;Timperley & Parr, 2009;Wohlstetter et al, 2008). A recent synthesis of the literature on professional learning that makes a difference to student learning and achievement found that schools that used data to inquire into School Effectiveness and School Improvementthe effectiveness of their teaching and school practices made significant improvements in achievement (Timperley et al, 2007).…”
Section: Rationale For Data-based Decision Makingmentioning
confidence: 99%
See 1 more Smart Citation